1988
DOI: 10.1080/00071668808417063
|View full text |Cite
|
Sign up to set email alerts
|

Digestibility of pentose sugars and uronic acids and their effect on chick weight gain and caecal size

Abstract: 1. In the first experiment D-xylose, L-arabinose, D-galacturonic and D-glucuronic acids were fed ad libitum to young chicks for 2 weeks at 200 g/kg of diet and weight gains and food consumption were recorded. 2. L-arabinose and D-xylose did not depress food consumption in the first week but prolonged feeding caused food consumption to decrease and weight gain to be adversely affected. 3. D-galacturonic acid and D-glucuronic acid caused severe growth retardation as early as the first week of feeding, primarily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

1991
1991
1995
1995

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 11 publications
2
15
1
Order By: Relevance
“…The relatively high concentration of arabinose in caecal contents here, after ic administration, may well explain the finding of Longstaff et al (1988) that caeca in broiler chicks fed on a basal diet supplemented with 50 g (L-) arabinose (or galacturonic or glucuronic acids)/kg were larger than with similar supplements of glucose, galactose or xylose. Furthermore, the treatments in their experiment that were associated with the largest caeca were also those where evidence of microbial fermentation in caeca was most apparent, reflecting conversion of substrate to volatile fatty acids (VFA).…”
Section: C Recoveries From Enzyme-treated U-14c-lahelled Festuca Cementioning
confidence: 55%
See 1 more Smart Citation
“…The relatively high concentration of arabinose in caecal contents here, after ic administration, may well explain the finding of Longstaff et al (1988) that caeca in broiler chicks fed on a basal diet supplemented with 50 g (L-) arabinose (or galacturonic or glucuronic acids)/kg were larger than with similar supplements of glucose, galactose or xylose. Furthermore, the treatments in their experiment that were associated with the largest caeca were also those where evidence of microbial fermentation in caeca was most apparent, reflecting conversion of substrate to volatile fatty acids (VFA).…”
Section: C Recoveries From Enzyme-treated U-14c-lahelled Festuca Cementioning
confidence: 55%
“…Third, metabolism of galacturonic acid derived from pectin, which accounted for 188 g/kg of the Festuca substrate, could not be included in the predicted response because no U-'4C-labelled galacturonic acid was available. However, judging from the results of Longstaff et al (1988), the metabolizable energy value of galacturonic acid is about half that of arabinose, so presumably its contribution to total 14C0, production with Festuca would also have been about half that of arabinose, since the concentrations of both residues in the Festuca material were about the same (188 and 179 g/kg respectively; C. J. Savoury, unpublished data). Hence, the contribution of galacturonic acid to the observed (wet enzyme) Festuca 14C0, response ( Table 2 ) should have been slight.…”
Section: C Recoveries From Enzyme-treated U-14c-lahelled Festuca Cementioning
confidence: 99%
“…Wagh & Waibel (1966) reported, that in chicks the ME value of D-xylose was decreased when the dietary level of this sugar was increased. Their finding may provide some evidence of an increased urinary excretion of D-xylose in percentage of intake when the dietary level of this sugar is increased, since Longstaff et al (1988) reported that apparent digestibility of D-xylose in chicks was nearly 100%. In the present study, urinary excretion of xylose as a percentage of intake increased when the dietary level of D-xylose was increased from 100 to 200 g/kg.…”
Section: Discussionmentioning
confidence: 97%
“…The lack of a positive effect of enzymes on the growth performance of chickens fed on lupin diets may be explained by the nature of the sugars liberated by enzymes. Lupin NSP contain about 22% galactose, 11 % D-xylose and 10% arabinose (Carre and Brillouet, 1986), which are poorly utilized by chickens as energy sources (Longstaff et al, 1988;Shutte et al, 1990).…”
Section: Discussionmentioning
confidence: 99%